Modeling and Computer Simulation of Viscoelastic Crypt Deformation - Oliveira, E. P.; Romanazzi, G. (Trends in Computational and Applied Mathematics, 2022)
Colorectal cancer morphogenesis begins at the cellular level from cell mutations in the intestinal epithelium cavities called crypts. These mutations lead to a pressure difference in the epithelium crypt walls, which causes deformation and generates visible abnormalities in the epithelium. The geometrical modeling of these crypts and the mathematical modeling of the physical process that cause the deformations can be simulated by using a Finite Element Method. The method solves numerically the system of PDE equations that governs this phenomenon and permits to estimate the deformations of the crypt walls. We simulate in this work the crypt deformation when the cell mutations appear in several regions of the crypt epithelium.